Activity of essential oils against Bacillus cereus spores and its application to extend the shelf life of cooked rice - M.S., Nur Shahera; Mahyudin, N.A.; Abdullah Sani, Muhammad Shirwan; Chong, Kah Hui; Jiangshan; Kousalya, P.; M.A.R., Nor Khaizura (Springer, 2025)
Bacillus cereus is a common foodborne pathogen associated with cooked rice. The sporicidal effects of Habbatus Sauda (HS), Lemongrass (LM), Black Pepper (BP), Oregano (OR) and Rosemary (RM) essential oils on B. cereus spores were investigated, along with their application in extending the shelf-life of cooked rice when stored at room temperature (30 °C). Various concentrations of each essential oil were used against B. cereus spore suspension, which was heated at different temperatures of 40, 70 and 100 °C for 30 min. Aside from RM, all essential oils effectively reduced > 1 log CFU/mL of B. cereus spores at 5% concentrations. Mixtures of rice, 5% of each essential oil of LM and OR and B. cereus spore suspension were cooked together to test the efficacies of LM and OR for application to cooked rice. LM EO showed higher potential in reducing both the vegetative and spore forms of B. cereus. With regard to this, 5% LM essential oil was applied to cooked rice to extend its shelf-life. The rice cooked together with 5% LM EO and B. cereus spore suspensions were stored at 30 °C for 6 days. The result demonstrated a higher reduction of Total Viable Count (TVC), Spore-former Count (SFC) and B. cereus Count (BC) as compared to the control. In conclusion, essential oils of HS, LM, BP and OR were proven to have a sporicidal effect against B. cereus spores. LM essential oil demonstrated the capability to extend the shelf-life of cooked rice from two days to six days.